Piękno i estetyka w matematyce - Melosik , Zbyszko (Studia Edukacyjne, 2021)
The article is devoted to the concept of beauty and aesthetics in mathematics. It first analyses the assumptions of rationality and objectivity of mathematics. In the second part, the article addresses the beauty and aesthetics in mathematical thinking and indicates profound skepticism in their validity. It likewise reconstructs the aesthetic dimension of Einstein’s theory. At the end, the author considers his own approach to aesthetics of theory in social sciences.